2001
DOI: 10.1016/s0022-5347(05)65646-7
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Stenting After Ureteroscopy for Distal Ureteral Calculi: A Multi-Institutional Prospective Randomized Controlled Study Assessing Pain, Outcomes and Complications

Abstract: Uncomplicated ureteroscopy for distal ureteral calculi with or without intraoperative ureteral dilation can safely be performed without placement of a ureteral stent. Patients without stents had significantly less pain, fewer urinary symptoms and decreased narcotic use postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
3
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(72 citation statements)
references
References 20 publications
9
53
3
7
Order By: Relevance
“…The same results were confirmed by Ibrahim et al [6] and Borboroglu et al [7] who found that patients without stents had significantly less bladder pain, urinary symptoms, and narcotic use postoperatively.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The same results were confirmed by Ibrahim et al [6] and Borboroglu et al [7] who found that patients without stents had significantly less bladder pain, urinary symptoms, and narcotic use postoperatively.…”
Section: Discussionsupporting
confidence: 62%
“…Borboroglu et al [7] in a multi-institutional prospective randomized controlled study were surprised to find a statistically significant lower incidence in flank pain in their patients without stents and explained it by the fact that perhaps the patients with stents had so much overall pain that they reflected this in response to the flank pain question.…”
Section: Discussionmentioning
confidence: 99%
“…Song ve ark. 'ları 1496 hastanın dahil edildiği bir meta-analizde 11 çalışmada stentli grupta %100 taşsızlık sağlandığını (12,13,15,(18)(19)(20)(21)(22), 1 çalışmada ise; stentsiz grupta %100 taşsızlık sağlandığını bildirmişlerdir (17). Diğer taraftan stentsiz gruplarda ise %97 oranında taşsızlık sağlandığı ve aradaki küçük farkın, fragmanların yetersiz düşürülme-sine bağlı olduğunu bidirmişlerdir (p>0.05) (14,23).…”
Section: Tartışılması Gereken Noktalarunclassified
“…Borboroğlu ve ark. 'ları da; çok merkezli randomize kontrollü prospektif bir çalışmada stent takılmayan grupta takılanlara göre anlamlı olarak daha az yan ağrısı olduğunu raporlamışlardır (15).…”
Section: Tartışılması Gereken Noktalarunclassified
“…17 Ureteral stenting following uncomplicated URS is optional: several randomized prospective studies published since the 1997 AUA guideline document has demonstrated that routine stenting after uncomplicated URS may not be necessary. 18,19 It is well documented that ureteral stenting is associated with bothersome lower urinary tract symptoms and pain that can albeit temporarily, alter the quality of life 20,21 besides, their complications associated with ureteral stenting, including infection, breakage, encrustation, and obstruction. Moreover, ureteral stents add some expense to the overall ureteroscopic procedure, and unless a pull string is attached to the distal end of the stent, secondary cystoscopy is The current study of ureteroscopic management for ureteric calculi displayed an outcome and complications comparable with other recent reports.…”
Section: Success Ratementioning
confidence: 99%